Stage Characteristics and Mechanisms of Extreme High Temperature in China in Summer of 2022 - Chyi Dorina; He Lifu (应用气象学报)
Stage characteristics and thermodynamic mechanisms of the extreme high temperature in China in summer of 2022 are analyzed with conventional observations, automatic weather station observations and the fifth-generation European Centre for Medium-Range Weather Forecasts (ECMWF) atmospheric reanalysis data (ERA5). It shows that the extreme high temperature process has two different stages. In June, high temperature areas are concentrated in North China and Huanghuai Region. From July to August the high temperature weather remains stable in Sichuan Basin and the middle and lower reaches of the Yangtze River. The influence area, intensity and duration of the high temperature from July to August are significantly stronger than those in June. Two stages of extreme high temperature occur in the anomalous circulation background. The South Asian high controls the upper troposphere with significant positive anomaly. Dominant systems are the strong development of high pressure ridge in North China and the stable maintenance of the evidently strong high-pressure dam in subtropical regions. The sustained dispersion of Rossby wave energy from upstream to North China and the weakening of transient weather disturbances are main causes for the enhancement and stability maintenance of the North China high pressure ridge. The strong convection in tropical regions, the enhancement of atmospheric heat sources on the southern side of the Northwest Pacific subtropical high, the strong updraft near the intertropical convergence zone and sinking in subtropical high ridge line near 30°N are conducive to the westward extension, strengthening, and stable maintenance of the Northwest Pacific subtropical high. The thermodynamic diagnostic analysis shows that the strong warm advection in the lower troposphere and the diabatic heating anomaly in the boundary layer above than the climatology is the main cause of the high temperature in North China and Huanghuai Region, and the maintenance of high temperature mainly relies on the contribution of strong diabatic heating. The formation of the extreme high temperature in Sichuan Basin and the middle and lower reaches of the Yangtze River is caused by subsidence warming anomaly which is in the low troposphere and stronger than the climatology. The second stage of the high temperature is also affected by the diabatic heating anomaly in the boundary layer. Besides the diabatic heating, the contribution of adiabatic heating (subsidence warming) term in the extremely strong South Asian high control region cannot be ignored.